2015
DOI: 10.1021/acs.jpcc.5b06469
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Electronic Structure and Transport Properties of Zigzag Graphene Nanoribbons by Edge Functionalization with Fluorine

Abstract: In this work, we report a detailed study of the electronic structure and transport properties of mono- and difluorinated edges of zigzag graphene nanoribbons (ZGNR) using density functional theory (DFT). The calculated formation energies at 0 K indicate that the stability of the nanoribbons increases with the increase in the concentration of difluorinated edge C atoms along with an interesting variation of the energy gaps between 0.0 to 0.66 eV depending on the concentration. This gives a possibility of tuning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Using this approach, we can produce inhomogeneously functionalized graphene as evidenced by an increase in contrast around intrinsic bilayer areas ( Figure 1b) which differs from previous reports. [17,22] To identify the origin of this large change in morphology, we conduct Raman spectroscopic characterization before and after plasma exposure for both single-layer and bilayer graphene ( Figure 1c) (more information in Figure S2, Supporting Information). The absence of a Raman D-peak in pristine graphene signifies the high quality of the employed graphene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, we can produce inhomogeneously functionalized graphene as evidenced by an increase in contrast around intrinsic bilayer areas ( Figure 1b) which differs from previous reports. [17,22] To identify the origin of this large change in morphology, we conduct Raman spectroscopic characterization before and after plasma exposure for both single-layer and bilayer graphene ( Figure 1c) (more information in Figure S2, Supporting Information). The absence of a Raman D-peak in pristine graphene signifies the high quality of the employed graphene.…”
Section: Resultsmentioning
confidence: 99%
“…© 2020 Wiley-VCH GmbH gasses [17,22] and highlights the unique combination of physical and chemical processes involved (more details in Figure S3, Supporting Information). Surprisingly, however, bilayer graphene is retained after the etching process although it exhibits a prominent D peak at 1352 cm −1 indicating the appearance of atomic-scale defects and sp 3 bonding.…”
Section: (3 Of 6)mentioning
confidence: 99%
“…According to our energetics considerations (see details in Ref. [39]), monoand difluorination [48], and mono-oxidation are found to be the most favorable chemical edge modifications. For each of these contaminant groups, we mimic the experimental fabrication process by investigating the contact formation upon approach of the metal to the graphenic system (see the details in the Methods section).…”
Section: B Interface Reactivity Of Contaminated Contactsmentioning
confidence: 97%
“…4(a). Thus, the F 2 modification of the graphene edge, despite being energetically more favorable for isolated graphene [48], is not likely to occur under the influence of transitionmetal electrodes in edge-contacted topology. When Au is used, instead, the graphene edges (clean or contaminated) are not modified by the interaction with the metal.…”
Section: Resistance Characteristics Of 1d Contactsmentioning
confidence: 99%
“…It has been demonstrated that a large memory window can be obtained using the Ge-NPs embedded in dielectrics [20,21]. Moreover, the spatial distribution of discrete charge Several studies have demonstrated that nano-sized graphene structures, graphene nanodots, exhibit unique electronic properties on the edges, i.e., with zigzag and armchair structures [30][31][32][33][34][35], which are particularly favorable for functionalization. These graphenebased nanodots were patterned using either silica nanodots or polystyrene spheres as an etching mask [36][37][38].…”
Section: Introductionmentioning
confidence: 99%